PERANCANGAN LAYOUT TOKO DAN PLANOGRAM PADA RAK 16 DI UNIT SWALAYAN KOPERASI WANITA - LEOLITA, LAURENSIA (Universitas Katolik Widya Mandala Surabaya, 2012)
Planogram is one of fool used to organize and member retailers address the existing products on the shelves. This is done to make the store look more presentable, attractive, and more organized according to category. Women's self-Unit Cooperative needs a planogram to the arrangement on each shelf. Symptoms of the problem appeared on unit swalayan is a loss for the last 2 years. Symptoms can be analyzed using the Balanced Scorecard through four perspectives, namely, the financial perspective, customer perspective, internal business process perspective and learning and growth perspectives. Based on the symptoms of problems are found, there is one root of the problem in the self-service unit associated with internal business processes. The root problem is the lack of self-planogram on the unit. The design is made planogram comprises the steps are slow and fast moving count, categorize products based on category management, store layout and design to make planogram. Therefore, the need for self-service unit for structuring planogram stores to be more organized and make it easier to organize workers and consumers in finding products.